PERKEMBANGAN FISIK MOTORIK ANAK: STTPA Tidak Tercapai - Titis Ema Nurmaya (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2017)
This article research discusses the physical motor development of children whose STTPA is not achieved. This research hold at TK AT Tauhid Pageralang in March 2017. This research is a qualitative research. The subjects of this study were 1 child of Group B TK AT Tauhid Pageralang who was 6 years old. The data were obtained by referring to subjects observation in the learning and adjusted to the standard of level achievement of the prescribed child of the kindergarten. The results of this study indicate a problem that inhibits the physical development of the subject motor, especially in the soft motoric development of subjects that have not been achieved. The inhibiting factor is that subjects have not been able to draw meaningful shapes and have not colored them neatly.Keywords: Physical Motor Development, AUD